Marketing and technology resource complementarity: an analysis of their interaction effect in two environmental contexts - Song, Michael; Droge, Cornelia; Hanvanich, Sangphet; Calantone, Roger (Strategic Management Journal, 2005)
Abstract The dynamic capabilities perspective posits that a firm can leverage the performance impact of existing resources through resource configuration, complementarity, and integration, but little empirical research addresses these issues. We investigate the effects on performance of marketing capabilities, technological capabilities, and their complementarity (interaction), and whether these effects are moderated by low vs. high technological turbulence. Results from SEM two‐group analyses (with controls) show that both main effects positively impact performance in both environmental contexts. However, (1) their interaction effect is significant only in the high‐turbulence environment; (2) the marketing‐related main effect is lower in the high‐turbulence environment; and (3) the main effects of technology‐related capabilities are the same in both environments. Our research suggests that the synergistic performance impact of complementary capabilities can be substantive in particular environmental contexts: while synergistic rents cannot always be obtained, it is possible to leverage existing resources through complementarity. Copyright © 2005 John Wiley & Sons, Ltd.